2015
DOI: 10.1097/ncc.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Breast Self-examination and Health Beliefs in Grenadian Women

Abstract: Beliefs about health and BSE affect BSE uptake and are culture dependent. These data help identify the at-risk population to guide the development of targeted community-based and culturally appropriate breast screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…However, these women also perceived themselves as more susceptible to BCA, which caused increased perceived barriers to performance. 11 Like the common findings of shame and desire for privacy in articles about CBE and mammography, a sample of Chilean women also identified BSE as a way to maintain privacy for themselves. 29 Two articles 13 , 27 found that Brazilian women who had more than 4 years of education were more likely to know about and perform BSE; conversely, in Trinidad, there was no apparent relationship.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…However, these women also perceived themselves as more susceptible to BCA, which caused increased perceived barriers to performance. 11 Like the common findings of shame and desire for privacy in articles about CBE and mammography, a sample of Chilean women also identified BSE as a way to maintain privacy for themselves. 29 Two articles 13 , 27 found that Brazilian women who had more than 4 years of education were more likely to know about and perform BSE; conversely, in Trinidad, there was no apparent relationship.…”
Section: Resultsmentioning
confidence: 91%
“…Findings among articles reviewed were not consistent about age and women’s attitude toward and tendency to perform BSE: One study found that younger women in Grenada tended to be more motivated to perform BSE 11 ; in Brazil and Mexico, though, older women were more likely to know about and practice BSE. 10 , 13 , 27 This is contrary to other findings from Brazil that older women tended not to know about or adhere to CBE.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Seven Caribbean countries contributed to six publications on behavioral factors relevant to BC. 83-88 Screening was associated with younger age and church attendance in Grenada 84 and general practitioner visits and provider communication in Guadeloupe and Martinique and the US Virgin Islands. 85,88 In Grenada, perceived susceptibility to BC and perceived benefit of screening were more likely to be associated with women who frequently attended church.…”
Section: Resultsmentioning
confidence: 99%
“…85,88 In Grenada, perceived susceptibility to BC and perceived benefit of screening were more likely to be associated with women who frequently attended church. 84 The only intervention study was conducted in Jamaica, where a theory-based educational intervention positively influenced knowledge of BC risk factors, symptoms, and types of screening and increased screening rates in screening-naïve women. 86 The two behavioral studies involving BC cases were conducted in Cuba and Puerto Rico; in Cuba, family history of BC was perceived as a risk factor, but the concept of genetic risk had little meaning 83 ; in Puerto Rico, patients with BC had low physical activity, despite access to exercise equipment and facilities.…”
Section: Resultsmentioning
confidence: 99%